(untitled) (OdontoInvestigación, 2021)
The aim of this study was to compare the number of cycles to breakage (NCF) of WaveOne Gold Primary (WOGP) and Reciproc Blue R25 (RBR25), after their use on root canals with 60° of curvature and radius (2 or 5mm). Therefore, four groups: 1° WOGP with a 2 mm. radius; 2° WOGP with a 5 mm. radius; 3° RBR25 with a 2mm. radius; and 4° RBR25 with a 5 mm. radius. of 5 files. Root canals were shaped with 60° and with a 2mm. and 5mm. radius, and time until file breakage was recorded and this is how the NCF was obtained. Cross section after file breakage was observed with an Endodontic Microscope. Group 4 had higher NCF, followed by group 3, group 2 and group 1. Both groups RBR25 had significant better cyclic fatigue resistance than WOGP.